Wave devouring propulsion for stabilizing floating wind turbine platform: experimental study - Xing, Jingru; Wang, Junxian; Matin, Ashkan; Vaidya, Ninad Prashant; Yang, Liang; Townsend, Nicholas; Zuo, Lei (Elsevier, 2025)
Wave Devouring Propulsion (WDP) is a green propulsion method that uses submerged foils to convert wave energy into thrust, serving both as an auxiliary propulsion system and as a stabilizer for maritime structures. This study highlights WDP's effectiveness in improving stability for semi-submersible offshore wind turbine platforms. Experiments on a 1:100 scaled model in regular and irregular head wave conditions were conducted in both free-floating conditions, and with a mooring system to validate WDP's effectiveness. Results show that the integrated foil design reduced mooring line tension by 41.07% compared to the design without foils in specific scenarios, suggesting a promising avenue for future research and application.
Keywords: Flapping foil; Wave-induced propulsion; Semi-submersible platform; Offshore wind; 4015 Maritime Engineering; 40 Engineering; 7 Affordable and Clean Energy; Civil Engineering; 4012 Fluid mechanics and thermal engineering